The impact of obesity on the outcome of severe SARS-CoV-2 ARDS in a high volume ECMO centre: ECMO and corticosteroids support the obesity paradox - Balik, M; Svobodova, E; Porizka, M; Maly, M; Brestovansky, P; Volny, L; Brozek, T; Bartosova, T; Jurisinova, I; Mevaldova, Z; Misovic, O; Novotny, A; et al. (Journal of critical care, 2022)
PURPOSE: The aim was to verify the impact of obesity on the long-term outcome of patients with severe SARS-CoV-2 ARDS. MATERIALS AND METHODS: The retrospective study included patients admitted to the high-volume ECMO centre between March 2020 and March 2022. The impact of body mass index (BMI), co-morbidities and therapeutic measures on the short and 90-day outcomes was analysed. RESULTS: 292 patients were included, of whom 119(40.8%) were treated with veno-venous ECMO cannulated mostly (73%) in a local hospital. 58.5% were obese (64.7% on ECMO), the ECMO was most frequent in BMI > 40(49%). The ICU mortality (36.8% for obese vs 33.9% for the non-obese, p = 0.58) was related to ECMO only for the non-obese (p = 0.04). The 90-day mortalities (48.5% obese vs 45.5% non-obese, p = 0.603) of the ECMO and non-ECMO patients were not significantly influenced by BMI (p = 0.47, p = 0.771, respectively). The obesity associated risk factors for adverse outcome were age <50 (RR 2.14) and history of chronic immunosuppressive therapy (RR 2.11, p = 0.009). The higher dosage of steroids (RR 0.57, p = 0.05) associated with a better outcome. CONCLUSIONS: The high incidence of obesity was not associated with worse short and long-term outcomes. ECMO in obese patients together with the use of steroids in the later stage of ARDS may improve survival.
Keywords: obezita; Obesity; Covid-19; Morbid obesity; Retrospective Studies; Corticosteroids; lidé; SARS-CoV-2 ARDS; hormony kůry nadledvin; COVID-19; SARS-CoV-2; Adrenal Cortex Hormones; retrospektivní studie; Extracorporeal membrane oxygenation; Respiratory Distress Syndrome; syndrom dechové tísně; Humans